Factors Affecting Non-Performing Financing at Islamic Commercial Banks in Indonesia - Retnowati, Ayu -; Jayanto, Prabowo Yudo (Accounting Analysis Journal, 2020)
This study aims to determine the effect of Inflation, Gross Domestic Product (GDP), Operational Income Operating Cost (BOPO), Financing to Deposit Ratio (FDR) and Capital Adequacy Ratio (CAR) to Non Performing Financing (NPF). The population in this study were 13 Islamic Commercial Bank in Indonesia in year 2012-2015. The sample selection used purposive sampling technique which resulted in 9 banks and the analysis units were 36. Data collection method used in this research was documentation. Data analysis method used was Structural Equation Modeling (SEM) with Partial Least Square (PLS) with SmartPLS 3.0 analysis tool. The results show that the inflation, GDP, and FDR variables do not significantly influence NPF. BOPO variable has a positive and significant influence to NPF. CAR variable has a negative and significant influence to NPF. The conclusion shows that the inflation, GDP, and FDR variables do not significantly influence NPF. Variables of BOPO and CAR have significant influence to NPF.